2021
DOI: 10.1002/adsc.202100339
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Domino Synthesis of 2,3‐Difunctionalized Indoles via Migratory Insertion of Isocyanides in Batch and Continuous Flow

Abstract: We report, herein, a palladium‐catalyzed cascade comprising carbopalladation, migratory insertion of isocyanide and triple bond activation followed by a nucleophilic attack (OR−) to construct difunctionalized acyl indoles. The process involves multiple bond formations via key palladium‐chemistry steps, to construct these bis‐heterocycles containing two privileged scaffolds (indole and oxindole) in a single operational step, along with attempts to generate enantioselectivity at a quaternary carbon center. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Later, a preliminary exploration of an enantioselective Heck/ isocyanide insertion reaction combined with triple bond activation and a final nucleophilic attack of N-(2-iodophenyl)-Nmethylacrylamide 300 with 2-(2-phenylethynyl)phenyl isocyanides 353 was presented by Sharma's group in 2021, affording 2,3-difunctionalized indoles with 73% ee (Scheme 77). 164 5.3.10. Heck/carbene insertion.…”
Section: Cyclization Via Heck Cascade Reactionmentioning
confidence: 99%
“…Later, a preliminary exploration of an enantioselective Heck/ isocyanide insertion reaction combined with triple bond activation and a final nucleophilic attack of N-(2-iodophenyl)-Nmethylacrylamide 300 with 2-(2-phenylethynyl)phenyl isocyanides 353 was presented by Sharma's group in 2021, affording 2,3-difunctionalized indoles with 73% ee (Scheme 77). 164 5.3.10. Heck/carbene insertion.…”
Section: Cyclization Via Heck Cascade Reactionmentioning
confidence: 99%
“…Palladium-catalyzed isocyanide insertion is the second approach to synthesize N -heterocycles from o -alkynylisocyanobenzenes. For instance, Yamamoto and Kamijo developed the synthesis of N -cyanoindoles via the palladium-catalyzed multicomponent coupling reaction from o -alkynylisocyanobenzenes in 2002 . Takemoto and coworkers successively reported the synthesis of indole and several tetracyclic indole derivatives from o -alkynylisocyanobenzenes under palladium catalysis in 2012 and 2013. , By means of a continuous-flow process to synthesize o -alkynylisocyanobenzenes in a telescopic manner, Sharma and coworkers developed an efficient synthetic method to prepare indole-based oxindoles from o -alkynylisocyanobenzenes under palladium catalysis in 2021 …”
Section: Introductionmentioning
confidence: 99%
“…The first concerns free-radical-initiated 5-exo or 6-endo cyclization of o -alkynylisocyanobenzenes; for example, Ogawa and coworkers continuously reported the synthesis of 2,4-bistellurated quinolines and 2, 4-diiodoquinolines from o -alkynylisocyanobenzenes through photochemical cyclization in 2009 and 2011. , Recently, Studer et al demonstrated a radical cascade to 2,3-disubstituted indoles via acylation or trifluoromethylation of o -alkynylisocyanobenzenes . Palladium-catalyzed isocyanide insertion is the second approach to synthesize N -heterocycles from o -alkynylisocyanobenzenes. For instance, Yamamoto and Kamijo developed the synthesis of N -cyanoindoles via the palladium-catalyzed multicomponent coupling reaction from o -alkynylisocyanobenzenes in 2002 . Takemoto and coworkers successively reported the synthesis of indole and several tetracyclic indole derivatives from o -alkynylisocyanobenzenes under palladium catalysis in 2012 and 2013. , By means of a continuous-flow process to synthesize o -alkynylisocyanobenzenes in a telescopic manner, Sharma and coworkers developed an efficient synthetic method to prepare indole-based oxindoles from o -alkynylisocyanobenzenes under palladium catalysis in 2021 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high affinity of isocyanide in coordinating with transition metals, a functionalized isocyanide has been applied successfully in palladium-catalyzed cascade reactions for the synthesis of a myriad of nitrogen heterocyclic motifs . In these reactions, a key imidoyl Pd­(II) intermediate is formed immediately after the generation of a Pd­(II) species via migratory insertion, followed by reaction with various intramolecular functional groups, such as amides, , aromatic C–H bonds, and alkynes . When an alkene-containing isocyanide is applied under palladium catalysis, sequential isocyanide and alkene insertion takes place selectively, leading to cyclic ketoimine derivatives .…”
mentioning
confidence: 99%